Torsional Response of Self-Excited Axially Compressed Thin-Walled Box Columns (Journal of Science and Technology, 2016)
Torsional response of self-excited axially compressed thin-walled box-columns is examined in this paper. Due to deficiency of Saint Venant's theory of torsion the basic equation of motion is derived using energy method on the basis of Vlasov's theory which allows combined treatment of pure and warping torsion. Investigation of the obtained equation reveals that torsional instability of the column is by divergence, and shear strains have significant effect on the modal frequencies of these columns and therefore must not be ignored in their dynamic analysis.